Diversity of Plant Communities Surrounding the Hot Springs on the Eastern Flank of the Sierra Madre Oriental, Northeastern Mexico - Jerjes R. Pantoja-Irys; Edilia de la Rosa-Manzano; José Guadalupe Martínez-Ávalos; Antonio Guerra-Pérez; Arturo Mora-Olivo; Leonardo U. Arellano-Méndez; Rocío Serna-Márquez; Edgar Daniel Salmerón-Carreño; Hugo Mujica-Sánchez (Biology)
Geothermally heated ecosystems experience extreme temperatures and play important ecological, cultural, and socio-economic roles in many environments. They support a diversity of plants that are often used by local communities. This study focused on five hot springs with varying geochemical traits in the northeast of Mexico. The diversity surrounding each hot spring was analyzed along with the impact of climatic factors. In total, we observed 2022 individual plants across 155 species and 55 families. Shrub strata dominated the rosetophyll scrub and low thorn forest, while tree strata were more common in the tropical dry forest; the herbaceous stratum exhibited the least diversity across all sites. A decrease in species richness was observed at higher elevations, while species abundance showed an inverse trend, being highest in the rosetophyll scrub. The plant communities exhibited clear differentiation in species composition with 30 indicator species identified across the five hot springs. Notably, only Helietta parvifolia was found in three sites. The variation in plant abundance was linked to elevation and evaporation. Each type of vegetation surrounding the hot springs demonstrates unique characteristics based on plant composition, suggesting that plant diversity may offer significant benefits to the surrounding communities in the northeast of Mexico.